The Impact of Markers of HIV Infection on Change in Liver Stiffness in People With HIV and Hepatitis C Virus Co-infection After Treatment and Cure of Hepatitis C. (15th December 2020) - van Santen, Daniela K.; Agius, Paul A.; Sasadeusz, Joseph; Fairley, Christopher K.; Sievert, William; Gane, Edward; Iser, David; O'Reilly, Mark; Medland, Nicholas A.; Moore, Richard; Hellard, Margaret E.; Hoy, Jennifer F.; et al.
Abstract : Background: Markers of HIV disease severity are associated with increased liver fibrosis in HIV/Hepatitis C virus (HCV) co-infected individuals. HCV treatment may reverse liver fibrosis, but evidence among HIV/HCV-co-infected populations and the impact of HIV parameters on fibrosis regression is limited. We aimed to assess the influence of surrogate markers of HIV-infection and other determinants of liver stiffness before HCV treatment and changes after HCV cure in people living with HIV. Methods: We used data from an HCV treatment implementation study aiming for HCV micro-elimination among gay and bisexual men with HIV in Melbourne, Australia (co-EC Study). We obtained liver stiffness measurements (LSM) before and after direct-acting antiviral treatment using transient elastography (FibroScan). Linear mixed models were used to evaluate determinants of pretreatment LSM and changes in LSM following cure with duration in years between pre- and post-LSM assessment as main exposure variable. Results: At least one LSM was available in 173 participants, and 98 participants had 2 LSMs. Median pre- and post-treatment LSMs were 5.7 and 5.1 kPa, respectively. Median time between transient elastography measurements was 1.3 years (interquartile range = 0.9–2.1). In multivariable analysis, longer duration of known HIV infection, a lower CD4 and CD8 T-cell count and hazardous alcohol consumption were associated with higher LSM values before treatment initiation. Successfully treated patients had a 6% (95% confidence interval = −10% to −2%) annual decrease (0.34 kPa predicted decrease) in LSM following cure. Changes in LSM values did not depend on any of the pretreatment HIV markers or other factors. Conclusion: Low levels of liver stiffness were observed before treatment initiation and a small decrease (6%) in LSM following HCV cure in people living with HIV. No clear predictors affecting change in LSM following cure were found in this study, including markers of HIV infection. However, markers of advanced HIV immunodeficiency and hazardous alcohol consumption remained associated with higher LSM values even after HCV cure. Abstract : Supplemental Digital Content is Available in the Text.